Industrial Relations in South Africa - Bendix, Sonia; Mthunzi Nxawe, Sharon Steyn, Alfred le Maitre, Lee-Ann Ashcroft, Marius Roux, Jennifer Stern, Lebone Publishing Services, DJE Flexible Print Solutions (Cape Town, South Africa: Juta & Co. Ltd, 2010)
Summary: Comparative industrial relations systems of USA, UK, Germany and Yugoslavia. Includes information on: Labour Relations Act 1995; Trade unions; Collective bargaining; Workplace forums; Lockouts; Workers' charter; Business charter.
Includes bibliographical references and index.
Adult
Keywords: South Africa